PENGARUH KOMPETENSI, PENGALAMAN KERJA DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI SURABAYA) (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
The study entitled Effect of competence, experience and independence of auditors working on the Quality Audit aims to examine and analyze the influence of competence, work experience and independence of the auditor to audit quality. The object of this study are all registered public accountant and worked in the Public Accounting Firm (KAP) in Surabaya with the minimum requirements have been working for a year at the KAP. Data were obtained from the data questionnaire with the data amount 60 respondents. The data analysis technique used is using validity, reliability, classic assumption test and multiple linear regression with SPSS for windows. The results showed that the variables of competence and work experience positive effect on audit quality, while independence has no effect on audit quality.